2006
DOI: 10.1007/s10681-006-9171-y
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium ear rot and how to screen for resistance in open pollinated maize in the Andean regions

Abstract: Ears infected with ear rot were collected from five provinces in Ecuador. Of the 44 samples analysed 26 carried Fusarium verticillioides, 11 F. subglutinans, two F. graminearum and five carried fungi different from Fusarium. The pathogenicity of ten isolates, seven of F. verticillioides and three of F. subglutinans, were tested. Per isolate 30 ears of the susceptible cultivar Mishca were inoculated by pricking a steel pin, dipped into a spore suspension, through the husks in the central part of the ear 14 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…2002). Silva et al. (2007) used 14 days in regular tests; later inoculations (19, 21 and 23 days after mid‐silking) resulted in significantly less disease severity.…”
Section: Resistance Components and Artificial Inoculationmentioning
confidence: 99%
See 1 more Smart Citation
“…2002). Silva et al. (2007) used 14 days in regular tests; later inoculations (19, 21 and 23 days after mid‐silking) resulted in significantly less disease severity.…”
Section: Resistance Components and Artificial Inoculationmentioning
confidence: 99%
“…Genotype differences are normally much larger for artificial inoculation regimes than for natural ones (Oberforster and Felder 2010). Silva et al. (2007) compared natural and artificial inoculation results and concluded that when only the husks were wounded, the sterile water control resulted in higher disease severity than the natural control.…”
Section: Natural Vs Artificial Inoculation Of Maize Earsmentioning
confidence: 99%
“…The hybrid × inoculation treatment interaction was significant for FUM and TW, indicating that the relative performance of genotypes for these traits differs under artificial and natural inoculation (Table 1). Hybrid × treatment interaction was not significant for FER, however, congruent with Silva et al (2007) and Eller et al (2010), who found no significant difference in the ranking of genotypes with and without inoculation. The entry mean-basis heritabilities for FER and FUM were 0.57 and 0.67 under artificial inoculation but reduced close to zero under natural conditions (Table 1).…”
Section: The Effects Of Treatment On Trait Means and Heritabilities In The Disease Evaluation Experimentsmentioning
confidence: 50%
“…n 6 9 63 ? n 7 9 88)/ P N, where n 1 -n 7 are the number of ears with scale values 1-7 which are multiplied with the mean percentage of the scale (Silva et al 2007). The diallel analysis of the 10 full-sib families were performed using Griffing's (1956) Method 1 fixed model, using the Diallel SAS-05 program (Zhang et al 2005) in the SAS computer package.…”
Section: Data Collection and Statistical Analysesmentioning
confidence: 99%